Diamond Fraud Dimension Analysis in Detecting Financial Statement Fraud in Companies Manufacturers Listed on the Indonesia Stock Exchange - Septhea Dwi Pratiwi; Imam Ghozali (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The aim of this research is to analyze and give the empirical evidence of the influence between fraud dimensions such as Pressure, Opportunity, rationalization, and Capability against Financial Statement Fraud. The population of this research is the manufacturing company listed on the Indonesian stock exchange in the period of 2017-2019. The researcher used purposive sampling as the method of choosing the sample with 302 data selections. For the data analysis, the researcher used multiple linear regression. The result of this research proved that financial stability has influenced to the financial statement fraud. The variable of external pressure has not been influenced to the financial statement fraud. Then the variable of financial targets has been influenced with the financial statement fraud. The variable of nature of industry has influenced to the financial statement fraud. Next, the variable of monitoring effectiveness has not been influenced to the financial statement fraud. The variable related party transaction has not been influenced to the financial statement fraud. The variable of auditor change has not been influenced to the financial statement fraud. The variable director change has not been influenced to the financial statement fraud.